Impact of H3.3 K27M Mutation on Prognosis and Survival of Grade IV Spinal Cord Glioma on the Basis of New 2016 World Health Organization Classification of the Central Nervous System. Issue 5 (1st May 2018) - Yi, Seong; Choi, Sunkyu; Shin, Dong Ah; Kim, Du Su; Choi, Junjeong; Ha, Yoon; Kim, Keung Nyun; Suh, Chang-Ok; Chang, Jong Hee; Kim, Se Hoon; Yoon, Do Heum
Abstract: BACKGROUND: Spinal cord glioma grade IV is a rare, diffuse midline glioma. H3 K27M-mutant was classified in a different entity in the 2016 World Health Organization (WHO) classification recently. No reports about prognosis of spinal cord glioma grade IV are available yet. OBJECTIVE: To analyze the prognostic factors for spinal cord glioma grade IV. METHODS: Twenty-five patients with spinal cord glioma of grade IV who underwent surgery in a single institute were selected. All grade IV spinal cord glioma histologically confirmed as glioblastoma or "diffuse midline glioma with H3 K27M-mutant" by the 2016 WHO classification of the central nervous system were included. Basic demographics, treatment modalities, and pathological tumor molecular profiles were investigated for prognosis. RESULTS: Mean age was 39.1 yr; male to female ratio was 18 : 7. Tumor was located in thoracic cord (53.3%), cervical cord (40%), and lumbar area (6.7%). Median overall survival was 37.1 mo; median disease-free survival was 18.5 mo. Treatment modality showed no statistical difference. Only K27M profile showed significant prognostic value, 20 patients (80%) showed K27M mutation positive, K27M mutation patients showed longer overall survival (40.07 mo) than K27M negative patients (11.63 mo, P  < .0001), and disease-free survival (20.85 vs 8.72 mo, P  = .0241). CONCLUSION: This study is the first and largest report of the prognosis of primary spinal cord grade IV glioma using the new WHO classification. This study reported survival analysis and prognostic factors, and revealed that H3.3 K27M mutation is not a major poor prognostic factor. Further studies to explore K27M mutations needed for risk stratification and therapy optimization.